Efektivitas Model Cooperative Problem Solving dengan Strategi Two Stay Two Stray terhadap Peningkatan Keterampilan Pemecahan Masalah Siswa pada Materi Energi Alternatif - Isna Multazam Zunnurrain; Hera Novia; Fitria Arifiyanti (Mataram University, 2026)
Low student’s problem-solving skills in the topic of alternative energy are reflected in their difficulties in understanding contextual problems and relating them to physics concepts. Therefore, the Cooperative Problem Solving (CPS) model integrated with the Two Stay Two Stray (TSTS) learning strategy was implemented as an alternative learning approach. This study is intended to analyze the improvement and the effect of integrating the TSTS strategy within the CPS model on students’ problem-solving skills. The research employed a quasi-experimental method with a Non-Equivalent Control Group Design involving two classes: an experimental class (CPS–TSTS) and a control class (CPS). The research instrument consisted of essay tests based on problem-solving skill indicators. The data were analyzed using N-gain calculation, independent sample t-test, and effect size analysis. The results indicate that both classes experienced improvement, with the average N-gain of the experimental class being 0.6722 and the control class 0.6250, both categorized as moderate. However, there was no significant difference in the improvement between the two classes. The integration of the TSTS strategy contributed to the improvement of students’ problem-solving skills, although the effect was still in the small category.